Atypical hemolytic uremic syndrome (aHUS) responsive to mycophenolate mofetil: A case report from Nepal. (December 2022) - Gurung, Jyoti; Regmi, Anil; Poudel, Bilash; Poudel, Ritu; Sharma, Rituraj; Pradhan, Sandip Raj
Abstract: Introduction: An atypical hemolytic uremic syndrome is an extremely rare and life-threatening thrombotic microangiopathy. This disorder is caused by dysregulation of the alternative pathway of the complement system in association with genetic abnormalities or the development of autoantibodies. However, 30–50% of patients do not have genetic or acquired mutations in the complement system. Case report: Patient presented with fever and periorbital swelling. She had anemia, thrombocytopenia, and deranged liver function tests. Urinalysis revealed hematuria and proteinuria. Antibody tests and genetic analysis were negative. Renal biopsy revealed findings suggestive of thrombotic microangiopathy with predominantly glomerular involvement. Thus, the diagnosis of Atypical Hemolytic Uremic Syndrome, immunofluorescence negative, genetic negative, and anti-complement negative was made. Discussion: This article reports a case of atypical hemolytic uremic syndrome in a child with negative genetic analysis and anti-complement factor H antibody, which was treated successfully on steroid and mycophenolate mofetil. Early diagnosis along with prompt treatment and close monitoring will lead to recovery from atypical Hemolytic Uremic Syndrome. Conclusion: Although HUS is generally associated with genetic abnormalities or a positive antibody test, some patients with HUS may present atypically with negative genetic analysis and antibody tests. Highlights: Hemolytic uremic syndrome (HUS) is a thrombotic microangiopathy. 5-10% of the cases of HUS is atypical HUS, mainly caused by abnormal activation of alternate complement pathway. Atypical hemolytic uremic syndrome results in a multi-organ system dysfunction, predominantly affecting the kidneys. Some patients with HUS may present atypically with negative genetic analysis and antibody tests.